2020
DOI: 10.2147/cia.s224224
|View full text |Cite
|
Sign up to set email alerts
|

<p>Predictors of Fall Protective Behaviors Among Iranian Community-Dwelling Older Adults: An Application of the Protection Motivation Theory</p>

Abstract: The protection motivation theory (PMT) is a common framework understanding the use of protective behaviors. The aim of this study was to assess the predictors of fall protective behaviors among community-dwelling older adults, Iran. Methods: The cross-sectional study was conducted in Qom, Iran, from May to October 2018. Three hundred older people were selected from retirement centers via stratified sampling method. Data were collected by a questionnaire containing items on socio-demographic information, Falls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 25 publications
1
26
1
Order By: Relevance
“…Overall, the response efficacy and self-efficacy are expected to reinforce coping appraisal, while the response cost is expected to reduce it (Fig. 1 ) [ 20 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the response efficacy and self-efficacy are expected to reinforce coping appraisal, while the response cost is expected to reduce it (Fig. 1 ) [ 20 ].
Fig.
…”
Section: Introductionmentioning
confidence: 99%
“…In the context of the COVID-19 pandemic, an excessive fear at the individual level can often lead to mental problems (Belen, 2020;Fountoulakis et al, 2020). However, a lack of fear may prevent individuals from participating in preventive measures to reduce the spread of COVID-19 (Gerritsenb, 2020;Taheri-Kharameh et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…In a cross-sectional study conducted in 10 countries during the COVID-19 pandemic, researchers found a statistically significant correlation between threat appraisal and preventive behavior (such as washing hands, wearing a face mask, and physical distancing) (Dryhurst et al, 2020 ). According to PMT, threat assessment is associated with fear (Miraja et al, 2019 ; Adunlin et al, 2020 ; Taheri-Kharameh et al, 2020 ; Rad et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…The mortality rate is 663540 cases. In Iran, 296273 people are a icted while 16,147 people died. In Hormozgan, these are, respectively, 19,934 and 516 cases (12).…”
Section: Introductionmentioning
confidence: 99%
“…Response e cacy and self-e cacy are expected to reinforce coping appraisal. To the contrary, response cost is expected to lower it ( Figure 1) (16) Fear is a moderating variable between perceived vulnerability, severity and threat appraisal. Thus, if one feels vulnerable to a serious health threat, the level of fear is increased and one is further motivated to adopt a preventive/protective behavior.…”
Section: Introductionmentioning
confidence: 99%